PENINGKATAN PATOGENESITAS VIRUS LATEN HASIL ISOLASI DARI KULTUR SEL MIDGUT LARVA SPODOPTERA LITURA TERHADAP LARVA SPODOPTERA LITURA MELALUI PENGINFEKSIAN BERULANG - IQBAL FILAYANI, MUHAMMAD Iqbal (LenteraBio: Berkala Ilmiah Biologi, 2013)
Nuclear polyhedrosis virus (NPV) is a virus of the family Baculoviridae that attack Lepidoptera. Nuclear polyhedrosis virus (NPV) were attacked S. litura called Spodoptera litura Nuclear Polyhedrosis Virus (SlNPV). SlNPV Propagation can be done by multiplication of the host's body (in vivo) and in the larval midgut cell cultures S. litura (in vitro). Propagation in cell culture midgut expressed latent virus generated from midgut cells S. litura. Latent virus is inactive virus in cell larval Latent virus has a very low pathogenicity. This study aimed to improve latent viral pathogenicity with recurrent infection at larval S. litura by in vivo. This research used larval S. litura second instar with 200 larval S. litura and latent virus concentration used 7.8 x107 PIBs/ml. is the results showed that the latent virus pathogenicity  increase if infection done repeatedly, the first infection gain mortality by 14%, the second infection gain  mortality by 63%, the third infection gain mortality by 90%.